An Improvement Technique Based on Structural Similarity Thresholding for Digital Watermarking. (17th December 2014) - Banitalebi-Dehkordi, Amin; Banitalebi-Dehkordi, Mehdi; Abouei, Jamshid; Nader-Esfahani, Said
Abstract : Digital watermarking is extensively used in ownership authentication and copyright protection. In this paper, we propose an efficient thresholding scheme to improve the watermark embedding procedure in an image. For the proposed algorithm, watermark casting is performed separately in each block of an image, and embedding in each block continues until a certain structural similarity threshold is reached. Numerical evaluations demonstrate that our scheme improves the imperceptibility of the watermark when the capacity remains fixed, and at the same time, robustness against attacks is assured. The proposed method is applicable to most image watermarking algorithms. We verify this issue on watermarking schemes in discrete cosine transform (DCT), wavelet, and spatial domain.